Fully bio-based poly(butylene succinate-co-butylene 2,5-thiophenedicarboxylate) with derived from 2,5-thiophenedicarboxylic acid - Guoqiang Wang; Xingyu Hao; Yakun Dong; Li Zhang; Rubo Sun (eXPRESS Polymer Letters, 2022)
Novel poly(butylene succinate-co-butylene 2,5-thiophenedicarboxylate) (PBSTFs) were successfully synthesized by changing the ratio of 2,5-thiophenedicarboxylic acid (TDCA) and 1,4-succinic acid (SA) through two-step melt polycondensation. Their structure, thermal properties, crystalline properties, mechanical properties, and rheological properties were tested and characterized. The glass transition temperature increases with the increase of butylene 2,5-thiophenedicarboxylate unit (BTF). NMR results show that the copolymers are random copolymers. Differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD) results show that all polyesters are semi-crystalline polymers. When the content of TDCA is 0–50%, the crystallinity and melting temperature of the samples decreased, Young’s modulus and tensile strength decreased, and the elongation at break increased obviously with the increase of BTF. When the content of TDCA is 50–100%, the tensile strength increases, but the elongation at break decreases slightly. The range of strength is between 15.4 and 38 MPa, and the maximum elongation at break can reach 1160%. Therefore, by adjusting the content of BTF, the structure of copolyesters can be adjusted to obtain fully bio-based copolyesters with excellent properties. Compared with poly(butylene succinate), when the molar percentage of TDCA in a product is 29%, the copolyester has better mechanical properties (tensile strength: 31.4 MPa and elongation at break: 1060%), higher glass transition temperature (–26.2 °C) and better processing properties.